Desenvolvimento de bebida prebiótica à base de amêndoa da castanha de caju e maracujá: aceitação e expectativa do consumidor - Rebouças, Marina Cabral (2012)
In function of the economic importance of cashew nuts to the state of Ceará, the largest producer and benefactor of the country, and the high percentage of broken kernels which decreases the profit expansion of this sector, it is necessary to search for new alternatives for use this product as a way of adding value to it. Thus, this research aimed to develop a prebiotic drink from the hidrossoluble extract of almond broken cashew nuts and passion fruit juice with added fructo-oligosaccharides, using response surface methodology for optimizing sensory attributes. Was evaluated the combined effect of the addition of passion fruit juice and fructo-oligosaccharides through an experimental design of the central composite rotational type, in the acceptance of the attributes of color, aroma, flavor, sweetness, viscosity and overall impression. The formulation more acceptable was characterized as to the moisture content, protein, lipids, carbohydrates and ash. The study of the stability of the beverage in refrigerated storage, was conducted over a period of 28 days through the analysis of pH, acidity, acceptance of the sensory attributes of color, aroma, flavor, viscosity and overall impression, determination of Coliforms at 35°C and 45°C, Salmonella sp. and mesophilic bacteria. Was also evaluated the acceptance of this drink in the face of commercial soy taste like passion fruit using the Hedonic Scale, Attitude Scale Purchase and Consumption, and preference through the paired comparison test. The consumer expectations was assessed by considering the claims of prebiotic drink. The most acepted prebiotic formulation of the drink contained 50% of passion fruit juice and 14% fructo-oligosaccharides, which has in its composition 79.42% moisture, 15.94% carbohydrate, 3.1% lipids, 1.36% protein and 0.18% ash. Based on the microbiological and sensory parameters the product can be marketed for a period of 28 days under refrigeration. The prebiotic drink almond cashew nuts and passion fruit juice showed similar performance in relation to sensory acceptance and preference when compared to commercial soy beverage. The prebiotic claims about the product caused a positive expectation on consumers, increasing acceptance. Therefore, it is safe to conclude that the prebiotic drink developed possesses nutritional composition and functional proper adequate, with satisfactory acceptability, showing potential for commercialization.